Three-dimensional subsurface defect shape reconstruction and visualisation by pulsed thermography - Sirikham, Adisorn; Zhao, Yifan; Liu, Haochen; Xu, Yigeng; Williams, Stewart; Mehnen, Jorn (Elsevier, 2019)
Defects detected by most thermographic inspection are represented in the form of 2D image, which might limit the understanding of where the defects initiate and how they grow over time. This paper introduces a novel technique to rapidly estimate the defect depth and thickness simultaneously based on one single-side inspection. For the first time, defects are reconstructed and visualised in the form of a 3D image using cost-effective and rapid pulsed thermography technology. The feasibility and effectiveness of the proposed solution is demonstrated through inspecting a composite specimen and a steel specimen with semi-closed airgaps. For the composite specimen, this technique can deliver comparatively low averaged percentage error of the estimated total 3D defect volume of less than 10%.
Keywords: Active thermography; 3D visualisation; Subsurface defects; Defect thickness